Association of vessel density with retinal sensitivity in patients with branch retinal artery occlusion - Rei Arasaki; Jacob Yuhang Chin; Tatsuya Inoue; Ryo Asaoka; Kazushi Hirono; Jared Ching; Shin Tanaka; Naoki Soga; Yasuo Yanagi; Maiko Maruyama-Inoue; Kazuaki Kadonosono (PLoS ONE, 2025)
Purpose To investigate the relationship between vessel density and retinal sensitivity in patients with branch retinal artery occlusion (BRAO). Methods This was a retrospective study of fourteen eyes of 13 BRAO patients. MP-3 microperimeter measurement and OCTA exams were performed at the same time. The exams were performed twice, one month and 6 months after the onset. The Early Treatment Diabetic Retinopathy Study (ETDRS) grid was superimposed onto the obtained images. We calculated the retinal sensitivity from MP-3 image, and vessel densities of superficial and deep capillary plexus (sVD and dVD) from OCTA images. These parameters were calculated for both the whole and parafoveal areas. A linear mixed model was used to investigate the correlations between retinal sensitivity and OCTA parameters. Results Mean retinal sensitivity was correlated only with sVD for both the whole and parafoveal areas at the first measurement (mR2=0.337, p<;0.001 and mR2=0.314, p<;0.001, respectively, linear mixed model). A significant correlation was also observed at the second measurement. Moreover, the sVD at the first measurement was significantly associated with retinal sensitivity at the final visit for the whole area (mR2=0.364, p<;0.001) and parafoveal areas (mR2=0.341, p<;0.001). Conclusions The retinal sensitivity of BRAO patients was correlated with the vessel density of superficial capillary plexus at both early and late periods. The superficial vessel density at the first visit was significantly associated with retinal sensitivity at the final visit, implying that early recovery of retinal blood flow is critical for maintaining visual function in RAO eyes.